NADPH-Oxidase Derived Hydrogen Peroxide and Irs2b Facilitate Re-oxygenation-Induced Catch-Up Growth in Zebrafish Embryo - Zasu, Ayaka; Hishima, Futa; Thauvin, Marion; Yoneyama, Yosuke; Kitani, Yoichiro; Hakuno, Fumihiko; Volovitch, Michel; Takahashi, Shin-Ichiro; Vriz, Sophie; Rampon, Christine; Kamei, Hiroyasu (Frontiers in Endocrinology, 2022)
Oxygen deprivation induces multiple changes at the cellular and organismal levels, and its re-supply also brings another special physiological status. We have investigated the effects of hypoxia/re-oxygenation on embryonic growth using the zebrafish model: hypoxia slows embryonic growth, but re-oxygenation induces growth spurt or catch-up growth. The mitogen-activated kinase (MAPK)-pathway downstream insulin-like growth factor (IGF/Igf) has been revealed to positively regulate the re-oxygenation-induced catch-up growth, and the role of reactive oxygen species generated by environmental oxygen fluctuation is potentially involved in the phenomenon. Here, we report the role of NADPH-oxidase (Nox)-dependent hydrogen peroxide (H2O2) production in the MAPK-activation and catch-up growth. The inhibition of Nox significantly blunted catch-up growth and MAPK-activity. Amongst two zebrafish insulin receptor substrate 2 genes (irs2a and irs2b), the loss of irs2b, but not its paralog irs2a, resulted in blunted MAPK-activation and catch-up growth. Furthermore, irs2b forcedly expressed in mammalian cells allowed IGF-MAPK augmentation in the presence of H2O2, and the irs2b deficiency completely abolished the somatotropic action of Nox in re-oxygenation condition. These results indicate that redox signaling alters IGF/Igf signaling to facilitate hypoxia/re-oxygenation-induced embryonic growth compensation.